Integration of Pollution Science and Environmental Engineering for the Development of Smart Systems to Treat Industrial Wastewater using Nanobiotechnology - Eliwy , Ola Bassim Abass; Mousa, Engy Shaheen Hassan; Habib , Elaff Mustafa Mahdi; Satt , Noor Ali Turki (American Journal of Botany and Bioengineering, 2025)
Pollution science investigates the nature, origin, extent, effects, control, and prevention of pollution. Environmental engineering applies these principles to develop technologies and systems that return the environment to its original state. Two engineering subcategories focused on sustainable technology are critical to this goal because an interdisciplinary approach to environmental protection is necessary. The search for sustainable technologies requires knowledge of pollution science, environmental engineering, and nanobiotechnology; the latter’s contributions are repeatedly emphasized. Smart systems—automation systems composed of sensors, data centers, and an increased use of the Internet of Things—have the potential to advance the treatment of industrial wastewater. They offer the capability of monitoring, collecting, analyzing, and utilizing real-time data for enhanced and innovative process maintenance and operation. Industrial wastewater requires the use of smart systems during treatment to ensure optimized performances and full compliance with legislation. Among new technologies, the offer of innovative nanoscale materials able to take advantage of their very large specific surface has boosted the use of nanobiotechnology for smart industrial wastewater treatments. The integration of these two scientific disciplines can advance the development of innovative and smart solutions for industrial wastewater management.